THE RELEVANCE OF KI HAJAR DEWANTARA’S EDUCATIONAL PHILOSOPHY IN 21ST CENTURY EDUCATION - Suparlan (Formad English Foundation NTB Jakarta, 2025)
This study aimed to examine the relevance of Ki Hajar Dewantara’s educational philosophy in the context of 21st-century education, particularly in the development of character and value-based humanistic education. In light of the rapid advancement of technology and the increasingly dynamic demands of education, it was considered essential to reassess the principles proposed by Ki Hajar Dewantara. A literature review method was employed using a qualitative approach to analyze scholarly works related to his thoughts and their application in contemporary education. The findings indicated that Ki Hajar Dewantara’s principles—such as Tut Wuri Handayani, the Among system, and the Tri Pusat Pendidikan (Three Centers of Education)—remained highly relevant for 21st-century education. These values supported character formation, learner autonomy, and an educational approach that emphasized independence, which were all crucial in addressing the challenges of education in the digital age. The study concluded that Ki Hajar Dewantara’s philosophy had made a significant contribution to the development of a more humanistic and relevant education system. The application of his values was found to strengthen character education and provide a strong foundation for the development of more inclusive curricula and educational policies in the future.